Characteristic temperatures of hypervelocity dust impact plasmas. Issue 9 (5th September 2016) - Collette, A.; Malaspina, D. M.; Sternovsky, Z.
Abstract: The effective ion and electron temperatures of dust impact generated plasma clouds are measured experimentally as a function of impact speed in the range of 4–20 km/s. The measurements are performed in an experimental setup that resembles the detection of dust particles by electric field or plasma wave antennas on spacecraft. The spacecraft is modeled as a conductive plate and a cylindrical antenna connected to voltage follower electronics is used to measure the collected charge. The setup is bombarded with dust particles using the University of Colorado IMPACT dust accelerator facility. The effective ion and electron temperatures are determined from the variation of the impact signals with an applied bias voltage. The results show that the temperatures of the electrons remain at around or below 5 eV over the investigated impact speed range. The characteristic ion temperature is about 5 eV at 4 km/s; however, it increases with increasing impact speed to > 10 eV at 20 km/s. Given that the floating potentials of spacecraft and antennas are on the order of a few volts, the findings suggest that any model for the interpretation of dust impact signals should take into account the effects of a finite temperatures. Key Points: The effective temperature of dust impact plasmas is measured experimentally The electron temperature remains below 5 eV for impact velocities below 20 km/s The ion temperature increases with impact velocity